Herwarth Walden und 3Der Sturm3 - Brühl, Georg (Köln : Dumont Buchverlag, 1983)
Adler, Egon ; Adrian-Nilsson, Gösta ; Albert, Karel ; Albrecht, Ernst Oskar ; Archipenko, Aleksandr ; Aron Fra Angek ; Arp, Hans (Jean) ; Asendorpf, Bartold ; Atkinson, Lawrence ; Balla, Giacomo ; Bauer, Rudolf ; Baum, Julie ; Baumann, Fritz ; Baumeister, Willi ; Bechtejeff, Wladimir von ; Begeer, F.A. ; Benes, Vincenc ; Bengen, Harold ; Berbereff, Christo ; Berlewi, Henryk ; Bernath, Aurel ; Biller, Vjera ; Birnbacher, Georg ; Bloch, Albert ; Boccioni, Umberto ; Boddien, Heinrich von ; De Boeck, Felix ; Bolz, Hanns ; Bortnyik, Sándor ; Bourgeois, Victor ; Brancusi, Constantin ; Braque, Georges ; Brass, Hans ; Braun, Nikolaus ; Bruce, Patrick Henry ; Bruguière, Francis ; Buchheister, Carl ; Buchholz, Erich ; Burger-Mühlfeld, Fritz ; Burljuk, David ; Burljuk, Vladimir Davidovic ; Busch, Paul ; Campendonck, Heinrich ; Capek, Josef ; Cernigoj, August ; Chagall, Marc ; Charchoune, Serge ; Charlot, Jean ; Chochol, Josef ; Ciacelli, Arturo ; Citroen, Paul ; d'Ebneth, Lajos ; Decker, G. den ; Delaunay, Robert ; Delaunay, Sonia ; Depero, Fortunato ; Dexel, Walter ; Duchamp-Villon, Raymond ; Eckertz, Waldemar ; Eggers, Alf ; Eingartner, Jacob ; Ensor, James ; Epstein, Elisabeth ; Ernst, Max ; Evola, Julius ; Exter, Alexandra Alexandrowna ; Feininger, Lyonel ; Felixmüller, Conrad ; Filla, Emil ; Fischer, Oskar ; Flaum, Franz ; Flouquet, Pierre ; Freundlich, Otto ; Friesz, Othon ; Fuhrmann, Paul ; Gauguin, Jean ; Gerlach, Karl ; Gestel, Leo ; Giannattasio, Ugo ; Gimmi, Wilhelm ; Gleizes, Albert ; Gocar, Josef ; Goedecker, Otto ; Goering, Reinhard ; Gontscharowa, Natalia ; Gordon, Mac Chouch ; Gris, Juan ; Grünewald, Isaac ; Gutfreund, Otto ; Haffenrichter, Hans ; Hald, Edvard ; Händel, Hugo ; Hartley, Marsden ; Hausmann, Raoul ; Heckel, Erich ; etc.
Duits
boek